Dual antiplatelet therapy pretreatment in IV thrombolysis for acute ischemic stroke. (11th September 2018) - Tsivgoulis, Georgios; Goyal, Nitin; Kerro, Ali; Katsanos, Aristeidis H.; Krishnan, Rashi; Malhotra, Konark; Pandhi, Abhi; Duden, Peter; Deep, Aman; Shahripour, Reza Bavarsad; Bryndziar, Tomas; Nearing, Katherine; et al.
Abstract : Objective: We sought to determine the safety and efficacy of IV thrombolysis (IVT) in acute ischemic stroke (AIS) patients with a history of dual antiplatelet therapy pretreatment (DAPP) in a prospective multicenter study. Methods: We compared the following outcomes between DAPP+ and DAPP− IVT-treated patients before and after propensity score matching (PSM): symptomatic intracranial hemorrhage (sICH), asymptomatic intracranial hemorrhage, favorable functional outcome (modified Rankin Scale score 0–1), and 3-month mortality. Results: Among 790 IVT patients, 58 (7%) were on DAPP before stroke (mean age 68 ± 13 years; 57% men; median NIH Stroke Scale score 8). DAPP+ patients were older with more risk factors compared to DAPP− patients. The rates of sICH were similar between groups (3.4% vs 3.2%). In multivariable analyses adjusting for potential confounders, DAPP was associated with higher odds of asymptomatic intracranial hemorrhage (odds ratio = 3.53, 95% confidence interval: 1.47–8.47; p = 0.005) but also with a higher likelihood of 3-month favorable functional outcome (odds ratio = 2.41, 95% confidence interval: 1.06–5.46; p = 0.035). After propensity score matching, 41 DAPP+ patients were matched to 82 DAPP− patients. The 2 groups did not differ in any of the baseline characteristics or safety and efficacy outcomes. Conclusions: DAPP is not associated with higher rates of sICH and 3-month mortality following IVT. DAPP should not be used as a reason to withhold IVT in otherwise eligible AIS candidates. Classification of evidence: This study provides Class III evidence that for IVT-treated patients with AIS, DAPP is not associated with a significantly higher risk of sICH. The study lacked the precision to exclude a potentially meaningful increase in sICH bleeding risk.